THE EFFECT OF HALAL CERTIFICATION AND HALAL VALUE CHAIN ​​ON THE COMPETITIVENESS AND SUSTAINABILITY OF UMKM SUPERIOR PRODUCTS IN PASURUAN REGENCY - Miftahul Huda; Nuraeni Nuraeni (International Journal of Nusantara Islam, 2026)
This study addresses enhancing competitiveness and sustainability of Pasuruan Regency's superior product MSMEs via halal certification and Halal Value Chain implementation. Amid globalization and rising halal awareness, MSMEs struggle with standards compliance, market access, and systematic supply chain support. The research identifies certification/value chain roles in boosting competitiveness and formulates sustainability strategies for the expanding halal ecosystem. The method used in this study uses the quantitative method of Path Analysis/Path Analysis with the type of Explanatory Research. By using the Attitude scale and providing a sample of 86 samples with Purposive Sampling Technique and the object in this study is MSME Actors of Superior Products in Pasuruan Regency. The results of this study are that the Halal Certification variable (X1) has a significant effect on  the Competitiveness  variable (Y1). The Halal Certification Variable (X1) does not have a significant effect on the Sustainability Variable of MSMEs of Superior Products in Pasuruan Regency (Y2). Self-control (X2) has a significant effect on Competitiveness (Y1). Self-control (X2) also has a significant effect on the Sustainability of MSMEs of Superior Products in Pasuruan Regency (Y2). The Competitiveness Variable (Y1) has a significant effect on the Sustainability of Superior Product MSMEs in Pasuruan Regency (Y2).